The Effects of Perceived Price, Quality, and Consumer Trust on Purchase Intentions of Halal Products - Ozkan, Bekir; Efendi?oğlu, İbrahim Halil; Baran, Tamer; Koç, Fatih (Springer Nature, 2024)
Consumption of halal products is preferred not only for religious requirements but also for the need to consume healthy products, both in places with a sizeable Muslim community and areas where non-Muslims live intensely. The increasing awareness of halal products amplifies the importance given to the subject and contributes to a growing number of academic studies on the matter. Consequently, elements such as price perception, quality perception, and trust for halal products evolve. This study aims to determine the impact of price and quality perception on halal product purchase intentions. Additionally, it seeks to explore the influence of price perception on trust. The questionnaire form prepared for this purpose was delivered to the participants online. After removing the erroneous data from the obtained dataset, a total of 340 data were used in the analysis. The data were initially objected to confirmatory factor analysis, followed by structural equation modeling which was performed to test the hypotheses. According to the results obtained, perceived price does not significantly affect purchase intentions, but it does positively affect perceived quality and consumer trust. Furthermore, perceived quality does not directly affect purchase intentions, yet it does affect consumer trust. Another key finding within the scope of the study is that consumer trust significantly influences purchase intentions. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.
14th Global Islamic Marketing Conference, GIMAC 2023 -- 2023-09-27 through 2023-09-29 -- Tbilisi -- 320499
Keywords: Consumer trust; Halal product; Perceived price; Perceived quality; Purchase intention